KEPEMIMPINAN KEPALA SEKOLAH DALAM MENINGKATKAN MUTU LAYANAN DITINJAU DARI TEORI KEPEMIMPINAN TRANSFORMASIONAL DI SDN SEMEMI II KOTA SURABAYA - Husniatul Nisak Muhammadun Putri; Sahudi Sahudi (STKIP Pesisir Selatan, 2026)
This study aims to analyze the principal's leadership in improving the quality of educational services based on the perspective of transformational leadership at Sememi II Public Elementary School, Surabaya. The focus of the study includes the implementation of four main dimensions, namely idealized influence, inspirational motivation, intellectual stimulation, and individualized consideration, and their relationship to the quality of educational services. The method used is a qualitative approach with a field research type, through observation techniques, interviews, and documentation of the principal, teachers, and students. Data analysis is carried out through data reduction, presentation, and drawing conclusions. The results of the study indicate that the principal has implemented transformational leadership effectively through exemplary behavior in building a school culture, motivating teachers to implement innovative learning based on PAIKEM, utilizing technology, and paying attention to the development of individual potential through extracurricular activities. This implementation has an impact on increasing student engagement, teacher performance, and creating a conducive learning environment. The novelty of this study lies in the integrative analysis between transformational leadership and the quality of educational services through the synergy of school culture, learning innovation, and the utilization of technology.